IMPROVING THE ABILITY OF MATHEMATIC LEARNING MOTIVATION CONNECTIONS WITH A CONTEXTUAL APPROACH - Batori, Batori; Hendriana, Heris; Maya, Rippi (IKIP SILIWANGI, 2018)
This study aims to determine the improvement of connection skills and motivation to learn mathematics by using a contextual approach and association between the two. The subjects of this study are students of SMP class VIII as much as two classes with 80 students. Instruments used in data collection are pretest and posttest for mathematical connection capability while for motivation to learn mathematics with posttest. Data on connection ability and mathematical learning motivation were analyzed using Mann Whitney nonparametric test. The result of this research is (1) Improvement of mathematical connection ability of junior high school students with learning using contextual approach better than those using ordinary learning. (2) The motivation of learning of junior high school student using contextual approach is better than using ordinary learning. (3) There is a strong association between the ability of the connection and motivation to learn the mathematics of junior high school students who are learning using a contextual approach.